The Role of Human Resources (HR) Training and Development in Improving Employee Performance in the Digital Era - Virra Islamia; Rahmatul Fitria; Meliana Febrianti; Anjelina Teresia Vinola (Escalate : Economics and Business Journal, 2026)
The development of digital technology has brought significant changes to the world of work and requires organizations to have competent, adaptive human resources (HR) who are able to utilize technology effectively. This study aims to analyze the role of HR training and development in improving employee performance in the digital era. The method used is a Systematic Literature Review (SLR) by examining various relevant scientific articles on training, HR development, digital competence, and employee performance. The results of the study indicate that training plays a significant role in improving employee knowledge, skills, and abilities in facing technological changes, while HR development contributes to shaping long-term capabilities, creativity, innovation, and employee readiness to face future challenges. In addition, the use of digital technologies such as e-learning, webinars, and Learning Management Systems (LMS) makes the learning process more flexible and effective.